Diseño de un manual para el sistema de control interno contable para la empresa Cronoenvíos Ltda. (2021)
With the business growth of societies and a highly competitive environment, companies have tended to make their production processes more efficient and improved and to be evidenced in their economic profitability in search of sustainability and growth in the market. The different processes and accounting records for this profitability to become tangible require vital tools in the proper management of the resources that a company has.